Platelet signaling in immune landscape: comprehensive mechanism and clinical therapy - Mengyao Yan; Zhe Wang; Zhiwei Qiu; Yimin Cui; Qian Xiang (Biomarker Research)
Abstract Platelets are essential for blood clotting and maintaining normal hemostasis. In pathological conditions, platelets are increasingly recognized as crucial regulatory factors in various immune-mediated inflammatory diseases. Resting platelets are induced by various factors such as immune complexes through Fc receptors, platelet-targeting autoantibodies and other platelet-activating stimuli. Platelet activation in immunological processes involves the release of immune activation stimuli, antigen presentation and interaction with immune cells. Platelets participate in both the innate immune system (neutrophils, monocytes/macrophages, dendritic cells (DCs) and Natural Killer (NK) cells and the adaptive immune system (T and B cells). Clinical therapeutic strategies include targeting platelet activation, platelet-immune cell interaction and platelet-endothelial cell interaction, which display positive development prospects. Understanding the mechanisms of platelets in immunity is important, and developing targeted modulations of these mechanisms will pave the way for promising therapeutic strategies.